Dampak Perubahan Laba ditinjau dari Return on Equity (ROA), Debt Equity Ratio (DER) dan Total Asset Turn Over (TATO) Pada Perusahaan Manufaktur di Indonesia - Rahmad Hidayat (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to determine the impact on earnings changes in terms of several aspects, namely return on equity (roe), debt to equity ratio (der), and total assets turn over (tattoos) in manufacturing companies on the Indonesian stock exchange in 2018-2021. This study uses a qualitative approach with secondary data sources obtained from the company's financial statements published on www.idx.co.id. The sampling technique in this study is the number of objects of companies listed on the IDX, where as many as 8 companies with data for 4 years so that the sample size is 32 data. The analysis carried out in this study is a panel data test which includes descriptive statistical analysis, Common Effects Model, Fixed Effects Model, Chow Test, Random Effects Model Test and Hausman Test (Software used to conduct this research is eviews version 10. Based on the results of the study it can be concluded that return on equity (roe), debt to equity ratio (der), and total assets turnover (tattoo) have partial and simultaneous effect on earnings changes, where the research that has been carried out obtains data taken based on the Common Securities Model